A review of the genus Dryinus Latreille, 1804 (Hymenoptera, Chrysidoidea, Dryinidae) from Iran, with description of a new species - Derafshan, Hossein Ali; Rakhshani, Ehsan; Olmi, Massimo (Zootaxa, 2016)
Three species of the genus Dryinus Latreille, 1804 from Iran are reviewed and keyed. Dryinus tamaricicola sp. nov. is described and illustrated. Dryinus tarraconensis Marshall, 1868 is newly recorded from Iran. Key to the Palaearctic species of Dryinus group 3 are modified.